Risk-Adjusted Performance of Mutual Funds: Evidence from China. Issue 9 (1st September 2016) - Gang, Jianhua; Qian, Zongxin
ABSTRACT: In this article, we evaluate the performance of mutual funds in China between 2006 and 2014. We first estimate time-varying abnormal returns of each mutual fund using an active peer benchmark-augmented factor pricing model. An index of riskiness is then estimated and used to calculate the augmented performance measure (APM). By construction, the APM separates the managerial premium of the fund from systematic risk premium, so it is better than the economic performance measure. The APM incorporates information beyond the first and second moments of the distribution of fund abnormal return; therefore, it is more informative than the Sharpe ratio.